Leaving Public Places: Antipolitical and Antipublic Forces of the Transnational Economy - Kantola, Anu (Javnost-The Public, 2001)
Over the last twenty years there has been a change of political regime from state controlled markets to market liberalisation. This article asks how are these changes affecting the role of the public sphere? The particular case is the economic crisis of Finland in the 1990s. The article looks at interviews of the country's most important political decision-makers: how do they perceive the role of politics and public in the new market regime? A new political culture favouring the market over the state, the private over the public and the experts over the politicians seem to appear. The elite interviews reveal an antipolitical and antipublic discourse, which tries to negate the relevance or to narrow the scope of public discussion. A formal transnational European democracy is not, however, a simple solution to these problems. The Finnish example shows how the antipublic forces of economic expertise and bureaucracy are emphasised also on the European level. Thus it is suggested that rather than choosing between national or transnational public sphere, we need to study how the public life is embedded in the structures of political power, how various political ideologies and powers aim at colonising or closing the public sphere.